Prevention of bullying across the moral education - Avilés M., José (2012)
The actions carried out in Spain are analyzed to approach the bullying from different areas in aspects of legislation, formation, spreading, awareness, prevention and intervention. Equally the preferential lines of action are emphasized in prevention and intervention in the school community affecting in the commitment and the coordination between the teachers and the families, making the students participate and cooperate in the solution as well as the facing of the bullying. The text examines about the keys of the moral education in relation with the components that identify the bullying, its coping with the skills and the necessary educational strategies to carry out the work in the cognitive, emotionally and behaviourally phases with the students on the part of the teachers and in collaboration and coordination with the families.